Evaluation of implementation of Enterprise Resource Planning System (ERP)and its impact on Accounting Practices (A Case Study in Metro Trading Company) - مكية نغم (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This study aims to evaluate the implementation of Enterprise Resource Planning System (ERP) and its impact on accounting practices in Metro trading company, to achieve that, a case study was inducted. Data were gathered by structured and unstructured interviews and direct observation, studying documents, and questioners were distributed to the accountants in the company. The findings indicate that: The study pointed out that ERP implementation in accounting practices lead to the expected benefits, reduce the time of reports preparing and improve the quality of data and reports, and reduce the depending on Excel program. The research recommends that it is important to make use of the benefits offered by the system like the planning budgets, while including the analytical skills of the accountants, also there is an importance to perform a detailed guide about procedures as a reference to ensure that is no need for more training programs every time there is a change in personnel, which has positive impact by avoiding costs (non-productive costs).